Analisis Kesalahan Penggunaan Hyoogen â€œtemo iiâ€ Dalam Bahasa Jepang Pada Mahasiswa Upi Bandung - Juangsih, Juju; Aneros, Noviyanti (Bina Nusantara University, 2011)
This research will study the use of â€œtemo iiâ€ of 31 students seventh semester in UPI. This studyÂ uses analysis descriptive method by collecting data from students to take 20 questions. It can beÂ concluded that the understanding of the use of â€œtemo iiâ€ of students show good scores about 53,39 %Â at average. There are three students who get 14 points (70%) which is the highest score. On theÂ otherhand there is one student who gets 5 points (25%) which is the lowest score. Although the resultÂ shows they are above average, but some students still missuse the word â€œtemo iiâ€. Moreover, theyÂ think the word â€œbolehâ€ in Indonesia can be replaced by â€œtemo iiâ€. However, the word â€œbolehâ€ canÂ not usualy be defined by â€œtemo iiâ€.